2018
DOI: 10.1186/s12913-018-3425-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medication reviews on use of potentially inappropriate medications in elderly patients; a cross-sectional study in Swedish primary care

Abstract: BackgroundDrug use among the elderly population is generally extensive and the use of potentially inappropriate medications (PIMs) is common, which increases the risk for drug-related problems (DRP). Medication reviews are one method to improve drug therapy by identifying, preventing and solving DRPs.The aim of this study was to evaluate the effect of medication reviews on total drug use and potentially inappropriate drug use in elderly patients, as well as describe the occurrence and types of drug-related pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 32 publications
3
68
2
1
Order By: Relevance
“…We found an average of 7.5 recommendations per patient; all patients had at least one recommendation. This is higher than the average of 1.1-5.9 drug-related problems found in medication reviews performed jointly by a pharmacist and a GP, described in a literature review by Geurts et al [3,[22][23][24][25][26][27][28][29]. Other medication review studies reported between 84% and 98% of patients to have at least one drug-related problem compared with 100% in this study [22,25,29,30].…”
Section: Recommended Changes To Medicationcontrasting
confidence: 64%
“…We found an average of 7.5 recommendations per patient; all patients had at least one recommendation. This is higher than the average of 1.1-5.9 drug-related problems found in medication reviews performed jointly by a pharmacist and a GP, described in a literature review by Geurts et al [3,[22][23][24][25][26][27][28][29]. Other medication review studies reported between 84% and 98% of patients to have at least one drug-related problem compared with 100% in this study [22,25,29,30].…”
Section: Recommended Changes To Medicationcontrasting
confidence: 64%
“…Medication reconciliation at admission and discharge increased signi cantly in the intervention site in phase two in this study. Medication review has been reported to signi cantly improve the appropriateness of prescribing in aged care facilities [14,15] and primary health care [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the effect of interventions on medication safety for older people in the community or primary care settings [12][13][14][15], however this study evaluated the effectiveness of a pharmacist intervention for PWD inpatients and the effect on polypharmacy and PIMS. Medication safety for PWD is particularly important because of the risks associated with medications for PWD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low prevalence in our study may be attributed to the tertiary care centre, good knowledge and practice among the treating physicians. Good knowledge of drugs and review of medications by the primary physician may improve the use of inappropriate medications in elderly 22 .…”
Section: Discussionmentioning
confidence: 99%